Trace DNA Retrieval from Forensic Footwear Evidence - Sirichantrawongse, Kittisak (วารสารวิชาการอาชญาวิทยาและนิติวิทยาศาสตร์, 2016)
Footwear in forensic science is the evidence that provides important information which can be used in assisting criminal investigations in several facets, for instance, determining the type of footwear that has made the impression at the crime scene, establishing the origin of debris found on footwear and also identifying a person who has worn them. Forensic footwear evidence may come in various types at crime scenes such as sneakers, slippers, sandals, flip-flops, etc. In most cases where shoeprints were prevalent, forensic examiners would not only establish a link between the crime scene shoe impression with the specific piece of footwear by comparing the shoe impression against the shoes in question to determine whether or not the questioned shoes were at the crime scene or comparing them against the database (if available) but also prove who the wearer was through DNA analysis. According to Locard’s exchange principle which concerns physical contact between two surfaces stating that every touch leaves a trace. When two objects comes into contact, there will always be an exchange of physical traces between the two surfaces [1].For footwear, the wearer’s feet definitely come into contact with the shoes. Therefore, it is anticipated that the skin cells that having deposited in the footwear definitely belong to the wearer. DNA typing from those sloughed skin cells can be used to identify the person who has worn the footwear. Up to the recent years there has been a minimal research on forensic footwear evidence. In Thailand there was no publication on DNA analysis from footwear. Sport shoes and Flip-flops are relatively popular and not infrequent to be found at crime scenes. DNA analysts often look for trace DNA besides the blood stain. The consistency of DNA profile production results from these footwear as trace DNA evidence is never seen.